2015
DOI: 10.1021/ja510946c
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered n/p-Co-assembled Materials with Remarkable Charge Mobilities

Abstract: Controlling self-organization and morphology of chemical architectures is an essential challenge for the search of higher energy-conversion efficiencies in a variety of optoelectronic devices. Here, we report a highly ordered donor/acceptor functional material, which has been obtained using the principle of ionic self-assembly. Initially, an electron donor π-extended tetrathiafulvalene and an electron acceptor perylene-bisimide were self-organized separately obtaining n-and p-nanofibers at the same scale. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…6,29,30,5658 However, to date studies have often used polychromatic light, 32,57 sacrificial electron donors, 24 or did not report the individual behaviour of the sub-components, 16 making it difficult to assess if an active heterojunction was indeed aiding the separation of photogenerated charges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,29,30,5658 However, to date studies have often used polychromatic light, 32,57 sacrificial electron donors, 24 or did not report the individual behaviour of the sub-components, 16 making it difficult to assess if an active heterojunction was indeed aiding the separation of photogenerated charges.…”
Section: Resultsmentioning
confidence: 99%
“…28 Martín and co-workers co-assembled a PBI and a tetrathiafulvalene into a hydrogel using opposing charges on the molecules. 29 They reported that the co-assembled structures give long lived separated charge states due to suppressed recombination. Another organogel based system utilised PBI and trithienylenevinylene LMWGs, again using a heat-cool method for self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Eur.J.2015, 21,14030 -14035 www.chemeurj.org As amphiphilic building blocks for the assembly of the second hydrophilic shell of [TiO 2 ÀPAC 16 ]@shell 1-7 next to the known surfactants 1 and 2,w es ynthesized as eries of new functional dendritic amphiphiles 3-7.C ompounds 3-5 consist of positively chargedp yridinium moietiesa st he core units and negativelyc harged carboxylates in the periphery.I nt hese prototypes, the opposite charges are separatedb yaseries of covalent bonds and organized within segregated areas of the macromolecular architectures. [9,20] Amphiphiles 1 and 2,c ontaining either ap ositive or negative singly charged head group were investigated for comparison and, in particular, as simple model amphiphiles to demonstrate the success of this supramolecular umpolung concept. At the isoelectricp oint, no additional counterions are required for charge neutralization.…”
Section: Resultsmentioning
confidence: 99%
“…The atomic force microscopy images revealed coexistence of the long fibrillar structure for aggregate of 37 and the spherical nano‐objects for PCMB aggregate (Figure ). In a different approach, Martín and co‐workers reported ionic interaction mediated donor‐acceptor co‐assembly . They have used π‐extended tetrathiafulvalene (TTF) derivative as donor (38) and perylene diimide (PDI) derivative (39, 40) as acceptor where both contained ionic functional groups (Figure ).…”
Section: Discussionmentioning
confidence: 99%